1995
DOI: 10.1021/ja00149a037
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion-Enhanced Optical Yield and E/Z Ratio in Enantiodifferentiating Photoisomerization of Cyclooctene Included and Sensitized by .beta.-Cyclodextrin Monobenzoate

Abstract: Cyclodextrins (CDs), a series of cyclic oligomers of Dglucopyranose, are known to accommodate a variety of organic guests in their chiral hydrophobic cavities, forming inclusion compounds. Consequently, they have been applied widely to biomimetic chemistry as well as to separation science and technology, including chiral re~ognition.'-~ In sharp contrast to the well-documented stoichiometric and catalytic thermal asymmetric syntheses utilizing the CD's chiral c a v i t~, ' ,~,~-~* little effort appears to have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(42 citation statements)
references
References 1 publication
(1 reference statement)
0
40
1
1
Order By: Relevance
“…Indeed, the ee of produced 4E is significantly improved from nearly zero obtained with native β -CD 65 to 24% by using 6 -O -(methyl phthaloyl) -β -CD 67b as chiral sensitizer. 130 More recently, it was reported that the photoisomerization of 4Z sensitized by 6 -O -( mmethoxybenzoyl) -β -CD 67g gives a much better ee of 46%, which is the highest ever reported for analogous CD -based sensitizers. 124,128 In contrast, both ortho and para isomers 67f and 67h afford only poor enantioselectivity under the same reaction condition, revealing that a small difference in host structure can critically affect the optical yield and further that not only the choice of suitable host but also the fi ne -tuning of sensitizer structure are equally crucial for obtaining the best result in supramolecular photochirogenesis.…”
Section: -Mediated Chiral Intramolecular Photoreactionsmentioning
confidence: 95%
“…Indeed, the ee of produced 4E is significantly improved from nearly zero obtained with native β -CD 65 to 24% by using 6 -O -(methyl phthaloyl) -β -CD 67b as chiral sensitizer. 130 More recently, it was reported that the photoisomerization of 4Z sensitized by 6 -O -( mmethoxybenzoyl) -β -CD 67g gives a much better ee of 46%, which is the highest ever reported for analogous CD -based sensitizers. 124,128 In contrast, both ortho and para isomers 67f and 67h afford only poor enantioselectivity under the same reaction condition, revealing that a small difference in host structure can critically affect the optical yield and further that not only the choice of suitable host but also the fi ne -tuning of sensitizer structure are equally crucial for obtaining the best result in supramolecular photochirogenesis.…”
Section: -Mediated Chiral Intramolecular Photoreactionsmentioning
confidence: 95%
“…The strategy relies on the covalent linkage of benzoyl sensitizers to the rim (O -6 position) of α -, β -, or γ -CDs. 111,112 Particularly promising results have been reported for β -CD, which presents the best cavity size match, possessing a 6 -O -(3 -methoxybenzoyl) substituent, which gives ee ' s approaching 50% (Fig. 2.20 ).…”
Section: Templated Photoisomerization Reactions In Solutionmentioning
confidence: 97%
“…[20] Photoisomerization of (Z)-cyclooctene (1Z) mediated by sensitizer-modified CDs (Scheme 1) is the earliest example of an enantiodifferentiating supramolecular photosensitization. [21] Direct photoirradiation of a 1:1 complex of 1Z with native b-CD at 185 nm gives nearly racemic 1E in 0.5-1.5% enantiomeric excess (ee), revealing the poor photochirogenic ability of the native b-CD cavity for 1Z. [22] In contrast, the supramolecular photoisomerization of 1Z included and sensitized by a 0.1 equivalent of benzoyl-CD (4a) affords 1E in up to 11% ee.…”
Section: Catalytic Supramolecular Photochirogenesis With Cyclodextrinsmentioning
confidence: 99%
“…[22] In contrast, the supramolecular photoisomerization of 1Z included and sensitized by a 0.1 equivalent of benzoyl-CD (4a) affords 1E in up to 11% ee. [21] Since then, a series of sensitizer-modified a-, band g-CD derivatives 4b-m (Figure 1) have been prepared for investigating the supramolecular photoisomerization of 1Z, and cyclooctadienes (2ZZ and 3ZZ) (Scheme 1). [23][24][25][26][27][28][29][30][31] hν + A nice trick employed in this supramolecular photochirogenic sensitization system is that the sensitizing ability is turned on only when a guest substrate is included in the host cavity.…”
Section: Catalytic Supramolecular Photochirogenesis With Cyclodextrinsmentioning
confidence: 99%